SISTEM PERJANJIAN PENDAHULUAN JUAL BELI RUMAH DIKAJI DARI HUKUM POSITIF - Sarikun (Sekolah Tinggi Ilmu Hukum Awang Long, 2021)
Works and Public Housing of the Republic of Indonesia Number 11 / PRT / M / 2019 concerning the Preliminary House Purchase Agreement System (hereinafter referred to as the PUPR Ministerial Regulation). The preliminary sale and purchase agreement frames the law between the seller and the buyer in the Pre Project Selling system before the actual buying and selling executor can be achieved. There are rights and obligations between the seller and the buyer in accordance with the agreement stated in the agreement. Positive Law in Indonesia in terms of the preliminary sale and purchase agreement in its legal regulations. The issuance of the Regulation of the Minister of Public Works and Public Housing (Permen PUPR) Number 11 / PRT / M / 2019 concerning the Preliminary Agreement System for the Sale and Purchase of Houses, brings justice, this regulation presents the State in protecting consumers. Basically, the legal force of the contract of sale and purchase agreement of land. The state is present and this regulation is proof that the state is here to protect the people, especially in terms of home buyers or consumers who are vulnerable to being exploited by housing developers because of their unfavorable position due to their status as buyers who cannot regulate from the developer or housing developer itself. The inverse comparison with a developer or housing developer who has the power or power to regulate consumers.